Taxonomic Study and Bioprospecting Indonesian Termitomyces eurrhizus - Ayu, Siti Maulyda; Mahardhika, Wahyu Aji; Putra, Ivan Permana; Nurhayat, Oktan Dwi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Termitomyces are known as wild edible mushrooms that are commonly consumed in Africa and Asia. T. eurrhizus can be easily found in many areas in Indonesia. However, the recent collection and proper documentation of this species has not been done in Indonesia. In addition, the potential utilization of this species needs to be revealed. This research aims to identify, investigate the proximate value, and test the antibacterial activity of T. eurrhizus. The exploration was carried out at the IPB University campus forest using an opportunistic sampling method. Fresh basidiomata were used for morphological identification. Proximate analysis was done following AOAC method. Mushroom extract was subjected to antibacterial test against Enteropathogenic Escherichia coli. Our specimen was identified as T. eurrhizus based on pileus characters (macroscopically) and spore features under an electron microscope (microscopically). The proximate result showed that the moisture content was 13,70 %, the ash 13,66 %, total fat content 2,05 %, total protein content 27,73 % and fiber content 8,49 %. The investigated antibacterial was evaluated based on size of antibacterial zone for concentration 200 mg/ml extract (3,5 mm), 100 mg/ml (6,5 mm), 50 mg/ml (3,83 mm), 25 mg/ml (2,5 mm), and 12.5 mg/ml 6,33 mm. Our result showed the potential utilization of T. eurrhizus as nutraceutical food and antibacterial. Further research is expected to collaborate with various cultivation or product development fields.